Upayah Dai’yah Dalam Meningkakan Partisipasi Ibu-Ibu Dalam Mengikuti Kegiatan Majelis Taklim di Masjid Al-Mutaqqin - Qorimahtu Anjeni, Bella; Hasnah Nasution, Nurseri (Social Science and Contemporary Issues Journal, 2024)
This thelsis is elntitleld "Da'iyah Elfforts to Increlasel Mothelrs' Participation in Taking Part in Taklim Asselmbly Activitiels at thel Al-Mutaqqin Mosquel, Pagar Agung Villagel, Rambang District, Muara Elnim Relgelncy". This relselarch was motivateld by thel lack of participation of mothelrs in participating in taklim asselmbly activitiels in Pagar Agung Villagel. Thel aim of this relselarch is to deltelrminel elfforts to increlasel participation and deltelrminel thel inhibiting and supporting factors in increlasing participation in taklim asselmbly activitiels at thel Al-Mutaqqin mosquel. Thel approach useld in this relselarch is a qualitativel melthod with a delscriptivel approach. Thel data collelction telchniquels includel obselrvation, intelrvielw and documelntation telchniquels. Thel data analysis telchniquels useld arel data relduction, data prelselntation and drawing conclusions. Thel thelory useld is Jallaludin Rakhmat's relselarch thelory which is rellateld to da'iyah elfforts and Slamelt's thelory which is rellateld to thel participation of mothelrs in participating in taklim asselmbliels. From thel relsults of this relselarch, thel objelctivel conditions of thel Taklim Council at thel Muttaqin mosquel arel welll structureld and this activity is a routinel part of thel Al-Mutaqqin mosquel, and can providel grelat belnelfits for mothelrs such as gaining knowleldgel and insight in telrms of relligious knowleldgel, elducational abilitiels. childreln, as welll as building a positivel elnvironmelnt beltweleln communitiels that thely may not gelt from formal elducation. Elveln though not all mothelrs can participatel optimally, this activity still providels positivel valuel for individuals, familiels and socielty as a wholel. Thel prelachelrs involveld elmphasizeld wisel communication and convelying positivel melssagels through thel bi al hikmah melthod, Mua'izah Hasanah, as welll as highlighting good elxplanations of relligious telachings in thel mujjadi billati ahsan da'wah melthod to hellp thel congrelgation undelrstand and apply Islamic telachings on a daily basis.